Didymodon californicus (Pottiaceae), a new species from California, U.S.A. - Jiménez, Juan Antonio; Toren, David; Shevock, James R. (Phytotaxa, 2014)
Didymodon californicus is described as a new species from California, U.S.A. The new taxon is included in sect. Vineales (Steere) R.H. Zander, and characterized mainly by its large size, lanceolate leaves, plane margins throughout, the red to reddish orange color in KOH, costa ending below the apex, a hyaline area of rectangular cells on ventral surface of the costa, cross-section of the costa with numerous guide cells in 2–3 layers and without ventral stereids, and smooth to low-papillose laminal cells. Drawings and light microscope photographs of the main characters are given, and possible confusion with other closely related taxa is discussed.